IN TEACHING ART TO STUDENTS THE SIGNIFICANCE OF ENVIRONMENTAL EDUCATION - Abdirasilov Sunnatillo Fayzullayevich; Temirov Murodjon Anvarovich (American Journals, 2022)
An analysis of the current state of the topic shows that today the role of environmental cleanliness is reflected in the depiction of natural landscapes and the analysis of its theoretical and practical development.At the same time, the significance of nature in the development of the younger generation is shown in the analysis through the image.
Keywords: Nature, landscape, ecology, color, psychology, composition, fine arts.